2020
DOI: 10.1002/ijc.33441
|View full text |Cite
|
Sign up to set email alerts
|

Statin use and head and neck squamous cell carcinoma outcomes

Abstract: Head and neck squamous cell carcinoma (HNSCC) is a morbid cancer with poor outcomes. Statins possess anticancer properties such as immunomodulatory and anti‐inflammatory effects. The objective of our study is to identify the association between statin use among untreated HNSCC patients and overall death, disease‐specific death and recurrence. HNSCC patients were recruited to participate in the University of Michigan Head and Neck Cancer Specialized Program of Research Excellence (SPORE) from 2003 to 2014. Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 40 publications
6
21
0
Order By: Relevance
“…Our recently published study found that statins were protective for HNSCC outcomes, but this protective association was observed only among patients whose tumors were HPV-positive. 19 The findings from this manuscript support that the inverse association between statin use and outcomes among HPV-positive HNSCC previously reported by our group may be due to an effect of statins on TILs in patients with HPV-positive tumors. 19 The inflammatory and immunomodulatory effects of cancer are not clearly directional by cell type.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our recently published study found that statins were protective for HNSCC outcomes, but this protective association was observed only among patients whose tumors were HPV-positive. 19 The findings from this manuscript support that the inverse association between statin use and outcomes among HPV-positive HNSCC previously reported by our group may be due to an effect of statins on TILs in patients with HPV-positive tumors. 19 The inflammatory and immunomodulatory effects of cancer are not clearly directional by cell type.…”
Section: Discussionsupporting
confidence: 88%
“…Based on our previous research, we observed an association between statin use and HNSCC outcomes, but only among patients whose disease was HPV-positive. 19 We therefore wanted to assess if effect modification by HPV status was present (HPV-positive, HPV-negative, HPV status invalid/missing) for the statin-inflammatory marker associations. Statistical interaction was evaluated using the likelihood ratio test.…”
Section: Discussionmentioning
confidence: 99%
“… 6 A large single-institution retrospective study showed similar results. 7 When subgroup analyses were done to assess the effects of HPV status with HNSCC, overall survival was increased for patients taking a statin who were HPV positive or negative, while disease-specific survival was increased by statins only in patients with HPV-positive disease. 7 In a retrospective study using the SEER Medicare database, Gupta et al classified patients with HNSCC as having hyperlipidemia plus using a statin, having hyperlipidemia but not using a statin, or not having hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
“… 7 When subgroup analyses were done to assess the effects of HPV status with HNSCC, overall survival was increased for patients taking a statin who were HPV positive or negative, while disease-specific survival was increased by statins only in patients with HPV-positive disease. 7 In a retrospective study using the SEER Medicare database, Gupta et al classified patients with HNSCC as having hyperlipidemia plus using a statin, having hyperlipidemia but not using a statin, or not having hyperlipidemia. Patients with hyperlipidemia who were taking a statin had increased overall and disease-specific survival versus those with hyperlipidemia not taking a statin and those without hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation